192k views
1 vote
Can someone help me?

Can someone help me?-example-1

1 Answer

3 votes

B.
√(x) + √(x - 1)


\large\mathfrak{{\pmb{\underline{\red{Step-by-step\:explanation}}{\orange{:}}}}}


(1)/( √(x) - √(x - 1) ) \\ \\= (1)/( √(x) - √(x - 1) ) * ( √(x) + √(x - 1) )/( √(x) + √(x - 1) ) \\ \\ = \frac{ √(x) + √(x - 1) }{ ({ √(x) })^(2) - { (√(x - 1) })^(2) } \\\\ [∵(a + b)(a - b) = {a}^(2) - {b}^(2) ] \\ \\= ( √(x) + √(x - 1) )/(x - (x - 1)) \\ \\= ( √(x) + √(x - 1) )/( x - x + 1) \\ \\= √(x) + √(x - 1)


\bold{ \green{ \star{ \orange{Mystique35}}}}⋆

User Nicolas Bouvrette
by
6.0k points